Pembelajaran Rest WEB Service Dengan Framework Springboot - Ahmad Fauzi; Eko Harli; Tria Hadi Kusmanto (Ikatan Ahli Informatika Indonesia, 2021)
Along with the rapid flow of information and communication as well as the increasing need for these two things, more and more media or information providers have emerged. The most important information for students or students' guardians is related to learning activities at school, such as information on grades, exam schedules, student attendance and others. Usually obtained when the school has announced it, and this information can be obtained only at the school. Currently, the development of programming languages ​​in Indonesia seems to be increasingly being carried out, including by educational institutions for the benefit of the teaching and learning process. In an effort to improve the efficiency of the development of programming languages ​​that contain elements of education, various alternatives and new innovations are needed in terms of making and developing programming languages ​​to be applied in the world of work for students. This is the basis for us to develop a WEB application-based information system using the SPRING framework which will be used as computer learning at SMKN 1 Depok and SMK Wira Buana 2 as a support for teaching and learning activities.